The Coordination Chemistry of f‐Block Elements in Molten Salts - Jiang, Shilin; Liu, Yalan; Wang, Lin; Chai, Zhifang; Shi, Wei‐Qun (Chemistry : a European journal, 2022)
The coordination chemistry of f‐block elements (lanthanide and actinide) in molten salts has become a resounding topic in view of its great importance to the research and development (R&D) of molten salt reactors and pyroprocessing. In this Review article, a general overview of the coordination chemistry of f‐block elements in molten salts is provided including past achievements and recent advances. Particular emphases are placed on the oxidation state, speciation, and solution structure of f‐block metal ions in molten salts, as well as their relationships with the salt composition. Furthermore, this review briefly discusses the spectroscopic and theoretical methods that complement each other in revealing the coordination properties. The coordination chemistry of f‐block elements in molten salts has become a resounding topic owing to fundamental interests and potential applications in molten salt reactors and pyroprocessing. This concept paper highlights the state‐of‐the‐art in the coordination chemistry of f‐block elements in molten salts, which may advance understanding of the nature of molten salt fuels, coolants and electrolytes.